The Effect of Self-Control, Self-Concept, and Lifestyle on Consumtive Behavior in Online Shopping on Students of Batam University - Fathonah, Siti; Ngaliman, Ngaliman; Luthfi, Andi M. (Universitas Batam, 2022)
The purpose of this study is to find out and analyze the effect of Self-Control, Self-Concept, and Lifestyle on Consumptive Behavior in Online Shopping at Batam University students. The method applied in this study is the quantitative method. The population in this study was students of Batam University with a total of 2,814 students at 2022. The sample of this study was 97 respondents. The data collection technique used in this study is a questionnaire which was tested for Validity and Reliability. The data analysis technique of this study uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this study used the SPSS Software version 25 program. The results of this study show that Self-Control has a positive and significant effect on Consumptive Behavior in online shopping for Batam University students with a probability value of 0.46 < 0.05. Self-Concept has a positive and insignificant effect on Consumptive Behavior in online shopping in Batam University students with a probability value of 0.138 > 0.05. Lifestyle has a positive and significant effect on Consumptive Behavior in online shopping for Batam University students with a probability value of 0.013 < 0.05. The coefficient of determination of 20.9% shows the contribution of Self-Control, Self-Concept, and Lifestyle to Consumptive Behavior in online shopping and the remaining 79.1% are explained by others relevant